State-owned enterprises face challenges in foreign acquisitions - Jing Li; Jun Xia (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2017)
State-owned enterprises (SOEs) have increasingly engaged in cross-border acquisitions. However, they face challenges related to regulatory approval in host countries, especially when they aim to acquire companies with rich R&D resources. Regulatory debates around the legitimacy of SOE acquisitions prolong acquisition duration and may also prevent acquisitions from being completed.
Keywords: 330